Taxation and internal migration: evidence from the Swiss census using community-level variation in income tax rates - Thomas Liebig; Patrick A. Puhani; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2006)
We investigate the relationship between income tax rate variation and internal migration for the unique case of Switzerland, whose system of determining tax rates primarily at the community level results in enough variation to permit analysis of their influence on migration. Specifically, using Swiss census data, we analyze migratory responses to tax rate variations for various groups defined by age, education, and nationality/residence permit. The results suggest that young Swiss college graduates are most sensitive to tax rate differences, but the estimated effects are not large enough to offset the revenue-increasing effect of a rise in tax rate. The migratory responses of foreigners and other age-education groups are even smaller, and reverse causation seems negligible.
urn:nbn:de:101:1-20090406233
Keywords: 330; Gemeindesteuer; Einkommensteuer; Binnenwanderung; Schweiz